Production and quality of 'Superior Seedless' grapes under irrigation restrictions during berry maturation - Marinho, Lígia Borges; Rodrigues, José Julio Vilar; Soares, José Monteiro; Coelho, Maria Auxiliadora Lima de; Moura, Magna Selma Beserra de; Brandão, Elieth Oliveira; Silva, Thieres George Freire da; Calgaro, Marcelo (Pesquisa Agropecuaria Brasileira, 2010)
The objective this work was to evaluate the effect of water deficit conditions, during the maturation phase of grapes, on the production and quality of the 'Superior Seedless', between July and November of 2007. The experiment was carried out in a randomized block design, with four replicates, in a (3x3) + 1 factorial arrangement: three times of alteration of the irrigation depths (21, 13 e 5 days before harvest); three irrigation depths (100, 50 e 0% of crop evapotranspiration); and a control treatment, which was the producer's irrigation management scheme. Irrigation timing and depth influenced berry firmness and titrable acidity. The management with cut-off irrigation depths at 13 or 21 days before harvesting and the control had the same yield, grape quality and water use efficiency, and may be adopted to save water for irrigation in the São Francisco Valley region.